Analysing The Influence of Company’s Dividend Policy and Financial Inclusion to Bank Risk and Performance - Erick Wijanarko; Antonius TP Siahaan (Conference Series, 2020)
This study examines whether company’s dividend policy and financial inclusion influences bank’s risk and performance in banking sector listed in Bursa Efek Indonesia during the period of 2013–2018 (6 years). Based on the analysis and hypothesis testing, this study showed the following results: Dividend Policy and Financial Inclusion has a significant impact on bank’s risk and performance. Furthermore, changes in dividend payments over time positively affect subsequent changes in foreign shareholding Method: This research used companies in banking sector listed in the Indonesia Stock Exchange as sample. Data was extracted from companies’ financial statements for the years 2013 to 2018 and BankFocus application. Impact of dividend policy is analysed by eViews software version 10 and data analysis is done through multiple regression analysis to test the hypothesis.